"Left behind?"- financialization and income inequality between the affluent, middle class, and the poor - Allen Hyde (Luxembourg Income Study (LIS), 2018)
There is increasing scholarly evidence that financialization has contributed to rising income inequality, especially by concentrating income among the affluent and rich. There is less empirical research examining who is losing out to the affluent. This paper fills this gap by examining how three measures of financialization (finance, insurance and real estate or FIRE employment; credit expansion; and financial crises) affect upper-tail (measured as the ratio between the 90th and 50th income percentiles) and lower-tail (measured as the ratio between the 50th and 10th income percentiles) income inequality. Using concepts from economic sociology and the social stratification literature, I develop a perspective that links financialization to income inequality by creating more unequal market incomes while simultaneously reducing redistribution and social transfers. I analyze disposable household income data (after taxes and transfers) from the Luxembourg Income Study (LIS) and other public sources like the OECD from 16 affluent nations between the years 1980 to 2010, and I use an unbalanced panel design due to LIS data coverage. I find that both the middle class and poor are hurt by financialization (strongest evidence tied to FIRE employment); however, incomes of the poor are most sensitive to financialization.
Keywords: 330; financialization; income inequality; income distribution; poverty; poor; low income